Studies of the resonance structure in D0→Kπ[minus-plus]π±π±π[minus-plus] decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2018)
Amplitude models are constructed to describe the resonance structure of D0→K−π+π+π−D0→K−π+π+π−{D^{0}→ K^{-}π ^{+}π ^{+}π ^{-}} and D0→K+π−π−π+D0→K+π−π−π+{D^{0} → K^{+}π ^{-}π ^{-}π ^{+}} decays using pp collision data collected at centre-of-mass energies of 7 and 8 TeV with the LHCb experiment, corresponding to an integrated luminosity of 3.0 fb−1fb−1fb^{-1}. The largest contributions to both decay amplitudes are found to come from axial resonances, with decay modes D0→a1(1260)+K−D0→a1(1260)+K−D^{0} → a_1(1260)^{+} K^{-} and D0→K1(1270/1400)+π−D0→K1(1270/1400)+π−D^{0} → K_1(1270/1400)^{+} π ^{-} being prominent in D0→K−π+π+π−D0→K−π+π+π−{D^{0}→ K^{-}π ^{+}π ^{+}π ^{-}} and D0→K+π−π−π+D0→K+π−π−π+D^{0}→ K^{+}π ^{-}π ^{-}π ^{+}, respectively. Precise measurements of the lineshape parameters and couplings of the a1(1260)+a1(1260)+a_1(1260)^{+}, K1(1270)−K1(1270)−K_1(1270)^{-} and K(1460)−K(1460)−K(1460)^{-} resonances are made, and a quasi model-independent study of the K(1460)−K(1460)−K(1460)^{-} resonance is performed. The coherence factor of the decays is calculated from the amplitude models to be RK3π=0.459±0.010(stat)±0.012(syst)±0.020(model)RK3π=0.459±0.010(stat)±0.012(syst)±0.020(model)R_{K3π } = 0.459± 0.010\,(stat) ± 0.012\,(syst) ± 0.020\,(model), which is consistent with direct measurements. These models will be useful in future measurements of the unitary-triangle angle γγγ and studies of charm mixing and CPCPC\!P violation.